2022
DOI: 10.21608/ejbo.2021.94145.1778
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Secondary Metabolites and Antimicrobial Activity of Plantago major L. from Egyptian Heterogenic Habitats

Abstract: Egyptian Journal of Botany http://ejbo.journals.ekb.eg/ 20 P LANTAGO major has been used to treat various diseases since ancient times. The present study aimed to assess the seasonal and habitat-related variations in the secondary metabolite content and antimicrobial activity of P. major leaf extracts. Eight habitats were selected for sampling plants in four seasons. The phytochemical screening of the ethanolic and chloroform extracts of P. major leaves from different habitats in different seasons showed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The 100 mg/mL concentration of ethanol extract had the highest inhibitory effect for P. aeruginosa with 22.6 mm inhibition zone. These results are in agreement with previous reports [25,26]. A study in Saudi Arabia demonstrated that P. aeruginosa was moderately sensitive to the ethanolic extract (95%) of P. major leaves with inhibition zone diameter of 12.5 mm [27].…”
Section: Discussionsupporting
confidence: 93%
“…The 100 mg/mL concentration of ethanol extract had the highest inhibitory effect for P. aeruginosa with 22.6 mm inhibition zone. These results are in agreement with previous reports [25,26]. A study in Saudi Arabia demonstrated that P. aeruginosa was moderately sensitive to the ethanolic extract (95%) of P. major leaves with inhibition zone diameter of 12.5 mm [27].…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, the freeze-dried hydroalcoholic extract was evaluated by HPLC and the chromatogram is presented in Figure 1. Plantago major L. extract is rich in tannins, flavonoids, caffeic acid, and other substances that demonstrate its efficacy to be used on skin wounds, which generates its antimicrobial and antifungal action [25].…”
Section: Composition Evaluation Of Plantago Major Extractmentioning
confidence: 99%
“…The activity is mainly attributed to its phytochemical components such as polysaccharides, lipids, derivatives of caffeic acid, flavonoids, iridoid glycosides, and terpenoids, offering anti-inflammatory, antioxidant, analgesic, immunomodulatory, anti-ulcer and antibiotic capacities. These pharmacological properties make it a promising phytochemical for biomedical and regenerative applications [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, methanolic extracts of Plantago major leaves showed higher antibacterial activity than aqueous and alcoholic extracts in studies conducted by Soliman et al (2022). A methanolic extract of Plantago major leaves from canal banks displayed the highest efficacy against P. aeruginosa , followed by an extract from orchards against Staphylococcus aureus [ 56 ]. Plantago major leaf extracts can inhibit microorganisms because they contain flavonoid components, phenols, tannins, and terpenoids, which all function together synergistically.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%